The essential revision guide to paediatric cardiology - Casans, Rebecca; Lal, Mithilesh; Griksaitis, Michael (Master pass, 2013)
This book is relevant to paediatricians in training, general practitioners, emergency department staff and specialist nurses. General staff working in specialist regional cardiac centres and healthcare professionals involved in the care of children and young people will also find this essential resource extremely useful. 'The aim of this handbook is to provide a rapid and reliable reference to congenital and acquired cardiac problems. It is very well organised. provides a more detailed discussion of cardiac physiology and pathophysiology and a comprehensive guide to ECG interpretation